KESIAPAN WARGA SEKOLAH DALAM MENGHADAPI BENCANA BANJIR BANDANG DI SMA NEGERI 2 BOGOR - Kasmila, Chyndy; Nefianto, Tirton; Lasmono, L (Jurnal Manajemen Bencana (JMB), 2019)
Disaster preparedness in schools is still on the minimum level, whereas schools necessarily are the centers of teaching and learning activities to give proper education for the nation’s better future. The purpose of this research is to analyze the preparedness of SMAN 2 Bogor to face flash flood disaster, and to analyze the impact of its occurrence. This research uses qualitative method, and the locus is Sukaresmi Village, Tanah Sareal Sub-district, Bogor City, West Java. The data is obtained from predetermined informants and analyzed by qualitative analysis technique. The parameters used in the analysis are knowledge and attitude parameters, policies and guidelines, emergency response plans, disaster warning systems, also resource mobilization. The results show that disaster preparedness in SMAN 2 Bogor is held by using various resources of school residents and supporting facilities, yet it has not been maximally done to increase the capacity of students and other elements of SMAN 2 Bogor. In general, schools only focus on the academic achievement, which ultimately leads to the lack of sensitivity toward people’s welfare needs. Awareness of disaster preparedness should not be owned only by the students, but also by educators, officials, and all elements of the school. However, this research analysis focuses more on the students. The unawareness of disaster preparedness planning is the main factor which makes the socialization and capacity improvement can not be done sustainably. Co-ordination and consultation with Provincial Government and Regional Disaster Management Agency is the necessary thing to do for the disaster prepardness planning.